Critical update, systematic review, and meta‐analysis of oral erythroplakia as an oral potentially malignant disorder - Lorenzo‐Pouso, Alejandro I.; Lafuente‐Ibáñez de Mendoza, Irene; Pérez‐Sayáns, Mario; Pérez‐Jardón, Alba; Chamorro‐Petronacci, Cintia M; Blanco‐Carrión, Andrés; Aguirre‐Urízar, José Manuel (Journal of oral pathology & medicine, 2022)
Background Oral erythroplakia has been classically considered as the potentially malignant disorder with the highest rate of malignant development into squamous cell carcinoma. This critical systematic review and meta‐analysis aim to estimate the malignant development rate of oral erythroplakia and identify the associated risk factors. Methods We performed a bibliographic search in PubMed, Scopus, Web of Science, Embase, and LILACS, with keywords “erythroplakia,” “erythroplasia,” “malignant transformation,” “malignant development,” “malignization,” “carcinogenesis,” “oral cancer,” “oral squamous cell carcinoma,” “mouth neoplasm,” and “prognosis.” Meta‐analysis was conducted using a random‐effects model. Results Ten observational studies with 441 patients met the inclusion criteria, whose mean malignant development rate was 12.7% and with a mean follow‐up period of patients of 6.66 years. In the initial biopsy, 42.8% of oral erythroplakia were already squamous cell carcinoma. The buccal mucosa was the most frequent location of oral erythroplakia, but the floor of the mouth was the most common site of malignant development. All patients who underwent malignant development showed epithelial dysplasia on the initial diagnostic biopsy. Conclusion Overall malignant development rate of OE in the meta‐analysis was 19.9%. We could not associate any specific clinicopathological feature with the malignant development. The presence of epithelial dysplasia in the initial biopsy remains the worst prognostic factor. Further observational studies on OE are needed, with well‐established diagnostic criteria and good clinical follow‐up, in order to identify the true risk of malignant development of oral erythroplakia and the related risk factors.